Strategi Pemberdayaan Ekonomi Masyarakat dengan Mengembangkan UMKM Keripik Jimpling Sebagai Antisipasi Terhadap Bank Emok di Kelurahan Sukamulya Tangerang - Satria Fajar Fatoni; Nindy Anggraeni; Putri Angggun; Rahmawati Nuriyah; Muhammad Rafli; Rohman Noraziz (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This article discusses the Religious Moderation Real Work Lecture (KKN) activities which were implemented using the Community Empowerment System (SISDAMAS) approach to optimize community empowerment through the development of micro, Small and Medium Enterprises (MSMEs) Chip Jimpling in Sukamulya Village. This is because businesses owned by the Sukamulya Village community have not developed optimally. The limited amount of income has resulted in the development of Emok Bank, which is a form of money lending practice with high interest and has the potential to be detrimental to society. The service method is carried out using community empowerment-based steps (SISDAMAS). There are 4 cycles that must be carried out, in cycle 1 students carry out community outreach and consultation, cycle 2 carries out social mapping, and cycle 3 is participatory. planning and community organizing, and Cycle 4 is program implementation and evaluation. The aim of this program is expected to be able to improve the local economy and reduce dependence on loans from Bank Emok. The results of this program show an increase in MSME income and public awareness of the importance of economic independence, so it is hoped that it can become a model of sustainable community empowerment.